Principle of proportionality as ground of judicial review: the jurisprudence in United Kingdom and Malaysia / Normawati Hashim - Hashim, Normawati (Universiti Teknologi MARA, 2020)
In state administration, the public authority has vast power, especially discretionary powers. If the powers are not closely scrutinized it is open for abuse. As a result, rights of an individual, which includes human rights would be affected. Thus, effective grounds of judicial review to protect human rights against abuse of powers by the authority must be effectively developed. One of the grounds of judicial review over action _ of the authority is principle of proportionality. According to the principle measure taken by the authority must be proportionate to the pursued objective. If it acted in excess of what is being required, the authority have acted disproportionately. Hence, the action or decision is invalid. Whether action or decision of the authority is proportionate or disproportionate, the court would decide. Hence, the court plays an essential role in developing jurisprudence on the application of principle of proportionality in judicial review. The principle of proportionality that has its originality in Prussia in the 19th Century is well developed and accepted under the European administrative law. Nevertheless, a different attitude was adopted in United Kingdom. The principle was not well accepted during the early years of its development. This is because the English courts belief that the review based on proportionality would touch the merit review of the administrative decisions and it was treated as part of Wednesbury unreasonableness. Nonetheless, when Wednesbury unreasonableness is insufficient to review the illegal act of the authority that infringe rights protected under the European Convention on Human Rights (ECHR) or Human Rights Act 1988 of an individual, the English judges began to develop jurisprudence on the application of principle of proportionality in judicial review. Eventually, the principle was accepted by the English Courts. The progressive development continued with the establishment of the three and the four steps structure test used in the review of action of the authority that infringed rights under ECHR or Human Rights Act 1988. However, the court did not tie itself to the three or the four steps structure tests in adopting the principle of proportionality as ground of judicial review. What the court look at is the application of proportionality in the sense of fair balance. Hence, what is important is to review the proportionate action of the authority so that a fair balance or proportionate balance is attain according to the objective to be achieved. If this is not achieved the action would be struck out as disproportionate, thus invalid. The Malaysian Court too recognized the principle of proportionality as one of the grounds for judicial review and this was illustrated in Tan Tek Seng v Suruhanjaya Perkhidmatan Pendidikan, Rama Chandran, R v The Industrial Court of Malaysia & Anor and Dr. Mohd. Nasir bin Hashim v Menteri Dalam Negeri. The flexible attitude of both the English and the Malaysian courts have contributed to the dynamic development of the jurisprudence of proportionality as one of the grounds in the review of unlawful act of the authorities in administration.